2011
DOI: 10.1242/jcs.072223
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA 376c enhances ovarian cancer cell survival by targeting activin receptor-like kinase 7: implications for chemoresistance

Abstract: MicroRNAs (miRNAs) are small noncoding RNAs that have important roles in gene regulation. We have previously reported that activin receptor-like kinase 7 (ALK7) and its ligand, Nodal, induce apoptosis in human epithelial ovarian cancer cells. In this study, we examined the regulation of ALK7 by miRNAs and demonstrate that miR-376c targets ALK7. Ectopic expression of miR-376c significantly increased cell proliferation and survival, enhanced spheroid formation and blocked Nodal-induced apoptosis. Interestingly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(86 citation statements)
references
References 50 publications
(51 reference statements)
1
85
0
Order By: Relevance
“…Current data suggest that miRNAs could render cancer cells susceptible or resistant to chemotherapy based on their functions and targets. 4,5 In ovarian cancer cells, examples include ectopic expression of miR-214-and miR-376c-enhanced cisplatin resistance through repression of PTEN and BAK1, respectively 39,40 ; overexpression of let-7i giving rise to an increase in cisplatin sensitivity 41 and dysregulation of miR-106a, miR-591 and miR-200c conferring paclitaxel resistance to cells by targeting BCL10 and caspase-7, ZEB1 and TUBB3. 5,42 These findings indicated that studies of miRNAs that target MDRrelated proteins would undoubtedly shed light on the therapeutic value of miRNAs in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Current data suggest that miRNAs could render cancer cells susceptible or resistant to chemotherapy based on their functions and targets. 4,5 In ovarian cancer cells, examples include ectopic expression of miR-214-and miR-376c-enhanced cisplatin resistance through repression of PTEN and BAK1, respectively 39,40 ; overexpression of let-7i giving rise to an increase in cisplatin sensitivity 41 and dysregulation of miR-106a, miR-591 and miR-200c conferring paclitaxel resistance to cells by targeting BCL10 and caspase-7, ZEB1 and TUBB3. 5,42 These findings indicated that studies of miRNAs that target MDRrelated proteins would undoubtedly shed light on the therapeutic value of miRNAs in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…During breast cancer invasion and angiogenesis, the ALK-4 mRNA is down-regulated by miR-98; because ALK-4 positively contributes to breast cancer metastasis, miR-98 acts as a metastasis suppressor (Siragam et al 2012). Finally, in ovarian cancers, the nodal/ALK-7 tumor suppressor pathway is inactivated by miR-376c, which down-regulates the ALK-7 receptor, showing that miR-376c has a protumorigenic effect (Ye et al 2011).…”
Section: Control Of Tgf-b Receptor Expression By Micrornasmentioning
confidence: 99%
“…Through binding to the 39-untranslated region (39UTR) of different target mRNAs (mRNAs), microRNAs can repress the translation of the target mRNAs (Seitz et al, 2003). As a new class of regulatory molecules, miRNAs have diverse functions in cell proliferation Viticchiè et al, 2011;Yu et al, 2012), survival (Fang et al, 2012a;Ye et al, 2011), invasion Luo et al, 2012;Siragam et al, 2012), cell differentiation (Goljanek-Whysall et al, 2012;Kahai et al, 2009;Rutnam and Yang, 2012b), morphogenesis (Wang et al, 2008a), tissue growth (Shan et al, 2009), angiogenesis Lee et al, 2007;Smits et al, 2010;Zou et al, 2012), tumor development (Nohata et al, 2012;Volinia et al, 2006) and metastasis (Huang et al, 2008;Ma et al, 2007;Rutnam and Yang, 2012a). The largest functional group of miRNAs is the one involved in cancer development.…”
Section: Introductionmentioning
confidence: 99%